Conjectured the behaviour of a recycled metal matrix composite (MMC-AlR) developed through hot press forging by means of 3D FEM simulation - Ahmad, A. (MDPI AG, 2018)
Melting aluminium waste to produce a secondary bulk material is such an energy-intensive recycling technique that it also indirectly threatens the environment. Hot press forging is introduced as an alternative. Mixing the waste with another substance is a proven practice that enhances the material integrity. To cope with the technology revolution, a finite element is utilised to predict the behaviour without a practical trial. Utilising commercial software, DEFORM 3D, the conjectures were demonstrated scientifically. The flow stress of the material was modified to suit the material used in the actual experiment. It is acknowledged that the stress-strain had gradually increased in each step. Due to the confined forming space, the temperature decreased by ~0.5 because the heat could not simply vacate the area. A reduction of ~10 of the flesh observed in the simulation is roughly the same as in the actual experiment. Above all, the simulation abides by the standards and follows what has been done previously. Through the finite element utilisation, this study forecasted the performance of the recycled composite. The results presented may facilitate improvement of the recycling issue and conserve the environment for a better future. Â© 2018 by the authors.